Trainee teachers' perception towards using first language to facilitate the teaching of an ESL classroom / Muhammad Faiz Mat Lazim - Mat Lazim, Muhammad Faiz (Faculty of Education, 2012)
This study intends to explore and investigate the perceptions of the trainee teachers' towards using first language to facilitate the teaching of an ESL classroom. This study aimed to discover the trainee teachers 'perception towards using first language to facilitate the teaching of English classes, the most popular approach in using first language to teach ESL classroom and also the limitations of using first language to facilitate the teaching of second language. 70 sets of questionnaires were distributed among the respective Semester 8 TESL students in UiTM Shah Alam Section 17 and all of it were returned back and were analyzed and also summarized. The results of the findings show that most of the trainee teachers' agreed that first language can be used to facilitate the teaching of an ESL classroom but with the proper method and some appropriate boundaries. It is because overuse of first language could bring negative effects to the students as well as to the teachers.